Indonesia’s Geothermal Resource Paradox: Unbundling Risks, Unleashing Private Capital - Ricardo G. Barcelona; Antonio de Wilde; Hanan Nugroho (Ministry of National Development Planning Republic of Indonesia/Bappenas, 2019)
The belief that resource abundance equates to energy security is roundly debunked in Indonesian geothermal. Indonesia’s copious geothermal reserves remain untapped. Experts cite the usual culprits: unreliable long-term contracts, ambivalent government support, and lukewarm investors investment appetite. In this paper, we argue that the real constraints lie in investors’ unresolved contradictions: Quick to complain about government’s unreliable and shifting stance, investors look to the same counter-party to guarantee their “iron-clad power purchase agreements (PPAs)” to secure their returns. To unleash Indonesia’s geothermal potential, we propose adopting slim-hole drilling technologies to reduce costs, while facilitating sequential commitments. This could enhance strategic flexibility that lowers the costs of good failures while facilitating the adoption of resource insurance to de-risk geothermal exploration and drilling. To sustain these benefits, “cheap” energy policy needs to be phased out to allow a restructured PT Perusahaan Listrik Negara’s (PLN) to flourish by embracing commercially viable strategic approaches.